"It didn't mean anything" – moving within a landscape of knowledge to interpret genetics and genetic test results within familial cancer concerns. Issue 4 (2nd October 2021) - Machirori, Mavis; Patch, Christine; Metcalfe, Alison
Abstract : Genetics is increasingly defining how we understand health and disease, affecting for some, their understanding of inherited disease, and the meaning of medical genetic information. When interpretations of hereditary conditions are determined, partly, by one's familial experience of heritable characteristics and partly by various other lived experiences, the meaning of genetics becomes highly personal. Through descriptions of stocks of knowledge, this paper describes findings from a qualitative study with a cohort of Black and Asian women with family and personal histories of cancer, about their interpretations of their genetic tests. We describe their interpretations as shaped by different experiences of biomedical practice as well as familial experiences of cancer and genetic testing; and we introduce a metaphor of "moving within a landscape, " to show how those interpretations were created and influenced by various sources of knowledge and life experiences.